PERAN PONDOK PESANTREN DALAM PENGEMBANGAN PENDIDIKAN AGAMA ISLAM DI NDONESIA - Sakdiah, Halimatun (Institut Syekh Abdul Halim Hasan Binjai, 2024)
This article aims to examine the role and contribution of Islamic boarding schools from their inception in Indonesia. Basically, Islamic boarding schools are Islamic educational institutions that have a different style from general educational institutions. Islamic boarding schools try to educate their students with various existing knowledge, both general knowledge and Islamic religious knowledge. Apart from that, Islamic boarding schools educate their students to have good manners and try to have a good impact on the presence of Islamic boarding schools in the scope of community life. And it is proven that Islamic boarding schools have a role and contribution in the history of the Indonesian nation and influence on Islamic religious education in Indonesia.